Real-Time Big Data Analytics - Gupta, Sumit; Gupta, Sumit; Shilpi (Packt Publishing, 2016)
Design, process, and analyze large sets of complex data in real timeAbout This BookGet acquainted with transformations and database-level interactions, and ensure the reliability of messages processed using StormImplement strategies to solve the challenges of real-time data processingLoad datasets, build queries, and make recommendations using Spark SQLWho This Book Is ForIf you are a Big Data architect, developer, or a programmer who wants to develop applications/frameworks to implement real-time analytics using open source technologies, then this book is for you.What You Will LearnExplore big data technologies and frameworksWork through practical challenges and use cases of real-time analytics versus batch analyticsDevelop real-word use cases for processing and analyzing data in real-time using the programming paradigm of Apache StormHandle and process real-time transactional dataOptimize and tune Apache Storm for varied workloads and production deploymentsProcess and stream data with Amazon Kinesis and Elastic MapReducePerform interactive and exploratory data analytics using Spark SQLDevelop common enterprise architectures/applications for real-time and batch analyticsIn DetailEnterprise has been striving hard to deal with the challenges of data arriving in real time or near real time.Although there are technologies such as Storm and Spark (and many more) that solve the challenges of real-time data, using the appropriate technology/framework for the right business use case is the key to success. This book provides you with the skills required to quickly design, implement and deploy your real-time analytics using real-world examples of big data use cases.From the beginning of the book, we will cover the basics of varied real-time data processing frameworks and technologies. We will discuss and explain the differences between batch and real-time processing in detail, and will also explore the techniques and programming concepts using Apache Storm.Moving on, we'll familiarize you with (3z(BAmazon Kinesis(3y (Bfor real-time data processing on cloud. We will further develop your understanding of real-time analytics through a comprehensive review of Apache Spark along with the high-level architecture and the building blocks of a Spark program.You will learn how to transform your data, get an output from transformations, and persist your results using Spark RDDs, using an interface called Spark SQL to work with Spark.At the end of this book, we will introduce Spark Streaming, the streaming library of Spark, and will walk you through the emerging Lambda Architecture (LA), which provides a hybrid platform for big data processing by combining real-time and precomputed batch data to provide a near real-time view of incoming data.Style and approachThis step-by-step is an easy-to-follow, detailed tutorial, filled with practical examples of basic and advanced features.Each topic is explained sequentially and supported by real-world examples and executable code snippets.s